1985
DOI: 10.1042/bj2250041
|View full text |Cite
|
Sign up to set email alerts
|

The role of ADP in the modulation of the calcium-efflux pathway in rat brain mitochondria

Abstract: The role of ADP in the regulation of Ca2+ efflux in rat brain mitochondria was investigated. ADP was shown to inhibit Ruthenium-Red-insensitive H+-and Na+-dependent Ca2+-efflux rates if Pi was present, but had no effect in the absence of Pi. The primary effect of ADP is an inhibition of Pi efflux, and therefore it allows the formation of a matrix Ca2+-P, complex at concentrations above 0.2mM-Pt and 25nmol of Ca2+/mg of protein, which maintains a constant free matrix Ca2+ concentration. ADP inhibition of Pi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…After the addition of Ca 2ϩ (40 nmol/mg protein, giving 5 M free Ca 2ϩ ), most of it was taken up by energized mitochondria. However, the total amount of Ca 2ϩ taken up after glutamate addition was higher in the absence than in the presence of Na ϩ (about 41 Ϯ 1.6 versus 26.6 Ϯ 3.7 nmol/mg protein in MSK and MSKNa, respectively), as observed previously with rat brain mitochondria (58,67). Interestingly, MAS activity measured in these two conditions varied inversely with the accumulated Ca 2ϩ .…”
Section: Activitysupporting
confidence: 82%
“…After the addition of Ca 2ϩ (40 nmol/mg protein, giving 5 M free Ca 2ϩ ), most of it was taken up by energized mitochondria. However, the total amount of Ca 2ϩ taken up after glutamate addition was higher in the absence than in the presence of Na ϩ (about 41 Ϯ 1.6 versus 26.6 Ϯ 3.7 nmol/mg protein in MSK and MSKNa, respectively), as observed previously with rat brain mitochondria (58,67). Interestingly, MAS activity measured in these two conditions varied inversely with the accumulated Ca 2ϩ .…”
Section: Activitysupporting
confidence: 82%
“…This effect was probably due to a stabilization of the PTP by ADP on the outer side of mitochondrial inner membrane. This effect has been demonstrated already in liver (Gizatullina et al, 2005) and brain mitochondria (Vitorica and Satrústegui, 1985;Brustovetsky et al, 2003). In conclusion, we assume that under physiological conditions BM, as mitochondria from other tissues, are sensitive to CsA.…”
Section: Csa Effects On Brain Mitochondriamentioning
confidence: 69%
“…4A, B, O). Also other authors have found that CsA effects on BM require low ADP concentrations (Vitorica and Satrústegui, 1985;Brustovetsky et al, 2003;Hansson et al, 2004). However, they used low ADP levels in combination with oligomycin in order to inhibit ADP phosphorylation to ATP.…”
Section: Csa Effects On Brain Mitochondriamentioning
confidence: 96%
See 2 more Smart Citations